Dual Synergistic Modulation of Photo-Induced Electron Transfer Processes Between Molecules and Gold Nanopillars for Ultrasensitive Plasmon-Enhanced Raman Scattering. - Ansah, Iris; Aranda, Daniel; Jung, Ho; Park, Sung-Gyu; Kang, Mijeong; Otero-Fernández-de-Molina, Juan Carlos; Kim, Dong-Ho (Royal Society of Chemistry, 2021)
This work presents a synergistic approach to boost plasmon- or surface-enhanced Raman scattering (SERS) by combining molecular and electrical modulators that fine-tune the electronic structure of metal−molecule interfaces, especially the charge transfer (CT) states, allowing molecular resonances. Paraquat (PQ2+) was interfaced with nanopillar SERS substrates whose surface excess of charge was modulated by intercalating anionic Au complexes (AuCl4−, Au(CN)2−) as well as by applying external electric potentials. Such concurrent dual modulation tuned the energy of the CT states of the substrate−anion−PQ2+ triads in resonance with the excitation laser, resulting in a large enhancement of the PQ2+ SERS bands. The results point to a novel coherent through-bond CT contribution of SERS, analogous to the superexchange mechanism for electron transfer in donor−bridge−acceptor systems. The large amplification enables high sensitivity for detecting PQ2+ and ultimately enables the on-site detection of PQ2+ in unprocessed real samples (coffee drink). This study account for new physicochemical variables affecting electron transfer processes in nanostructured metal-molecule interfaces and provides a path for further exploring chemical strategies for greater Raman enhancement and for developing ultrasensitive Raman platforms.
https://v2.sherpa.ac.uk/id/publication/25610 (Accepted version, pathway A)
Keywords: Efecto Raman de superficie intensificada; Transferencia de carga; SERS; Charge transfer; ELECTRODE